Effect of biochar on heavy metal accumulation in potatoes from wastewater irrigation. (15th February 2019) - Nzediegwu, Christopher; Prasher, Shiv; Elsayed, Eman; Dhiman, Jaskaran; Mawof, Ali; Patel, Ramanbhai
Abstract: In many developing countries water scarcity has led to the use of wastewater, often untreated, to irrigate a range of crops, including tuber crops such as potatoes ( Solanum tuberosum L.). Untreated wastewater contains a wide range of contaminants, including heavy metals, which can find their way into the edible part of the crop, thereby posing a risk to human health. An experiment was undertaken to elucidate the fate and transport of six water-borne heavy metals (Cd, Cr, Cu, Fe, Pb and Zn), applied through irrigation water to a potato (cv. Russet Burbank) crop grown on sandy soil, having either received no biochar amendment or having top 0.10 m of soil amended with 1% (w/w) plantain peel biochar. A non-amended control, irrigated with tap water, along with the two contaminated water treatments were replicated three times in a completely randomized design carried out on nine outdoor PVC lysimeters of 1.0 m height and 0.45 m diameter. The potatoes were planted, irrigated at 10-day intervals, and leachate then collected. Soil samples collected two days after each irrigation showed that all heavy metals accumulated in the surface soil; Fe, Pb and Zn were detected at 0.1 m depth, while only Fe was detected at 0.3 m depth. Heavy metals were not detected in the leachate. Tested individually, all portions of the potato plant (tuber flesh, peel, leaf, stem and root) bore heavy metals. Biochar-amended soil significantly reduced only Cd and Zn concentrations in tuber flesh (69% and 33%, respectively) and peel compared to the non-amended wastewater control ( p  < 0.05). Heavy metal concentrations were significantly lower in the tuber flesh than in the peel, suggesting that when consuming potatoes grown under wastewater irrigation, the peel poses a higher health risk than the flesh. Graphical abstract: Image 1 Highlights: Metal uptake by potato grown with wastewater in biochar-amended soil was studied. Irrigation with wastewater led to the accumulation of heavy metals in soil. Plantain peel biochar significantly adsorbed Cd and Zn in the soil. Plantain peel biochar significantly reduced Cd and Zn in potato flesh.